1997
DOI: 10.1074/jbc.272.26.16351
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Modulates a p53-independent Apoptotic Pathway and Apoptosis-related Gene Expression

Abstract: Interferon (IFN)- FLICE). Of the bcl-2 family members, IFN-␥ directly induced bak but notably not bax, which is activated by p53. The IFN-responsive transcriptional activator interferon regulatory factor-1 was also strongly induced and translocated into the nucleus following IFN-␥ treatment. We propose that IFN-␥ modulates a p53-independent apoptotic pathway by both directly and indirectly inducing select apoptosis-related genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
192
3
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(212 citation statements)
references
References 47 publications
15
192
3
1
Order By: Relevance
“…It is possible that this difference is cell line specific, or is influenced by the expression of recombinant proteins. For instance, the CHO IFN-c cell line in the study by Wong et al produces a recombinant human interferon gamma, which has been documented to activate Fas death receptor signaling (Curtin and Cotter 2003;Ossina et al 1997;Spanaus et al 1998). Therefore, the observed transcriptional changes in the CHO IFNc batch culture might not be universally applicable to other CHO cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this difference is cell line specific, or is influenced by the expression of recombinant proteins. For instance, the CHO IFN-c cell line in the study by Wong et al produces a recombinant human interferon gamma, which has been documented to activate Fas death receptor signaling (Curtin and Cotter 2003;Ossina et al 1997;Spanaus et al 1998). Therefore, the observed transcriptional changes in the CHO IFNc batch culture might not be universally applicable to other CHO cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that IRF-1 interacts with Signal Transducers and Activator of Transcription (STATs) to induce the expression of caspase genes (Kumar et al, 1997;Hoey, 1997). IRF-1 has been implicated also in apoptosis induced by IFNg in human colon adenocarcinoma HT-29 cells treated with various cytotoxic agents (Ossina et al, 1997), in apoptosis of serum deprived and angiotensin II treated R3T3 cells (Horiuchi et al, 1997), and apoptosis of PKR de®cient MEFs that were resistant to death induced by double-stranded RNA, TNFa, or LPS .…”
Section: Terminal DI Erentiation Negative Growth Control and Myd Genesmentioning
confidence: 99%
“…IRF-1 plays an important role in p53-independent response to DNA damage and is able to promote apoptosis in p53(À) cells (Tamura et al, 1995;Ossina et al, 1997;Porta et al, 2005). There is evidence that IRF-1 may act in parallel with p53 to promote apoptosis and therefore, loss of IRF-1 would promote the survival of HMECs that had acutely lost p53 function.…”
Section: Discussionmentioning
confidence: 99%
“…rECM promotes recruitment of CBP and STAT1 to the IRF-1 GAS element Type II-IFN (IFN-g) signaling has been shown to promote p53-independent apoptosis (Ossina et al, 1997;Porta et al, 2005). We previously demonstrated that treatment of *HMEC-E6 cells with 1.0 mM Tam promotes formation of a STAT1 complex on the IRF-1 GAS element, recruitment of cofactor CBP and upregulation of IRF-1 messenger RNA (mRNA).…”
Section: Recm-induced Gene Transcriptsmentioning
confidence: 99%